Composantes de l'outil GeOC. - Fradi, Fajr; Diwediga, Badabate; Le, Quang Bao; Bonaiuti, Enrico; Lala-Pritchard, Tana; Hemingway, Charlotte; Thomas, Richard (2017)
Under the Economics of Land degradation initiative (ELD), scientists from ICARDA are collaborating with developments to develop the GeOC tool. It is a new web-based GIS tool to define context specific options for sustainable land management required to achieve Land Degradation Neutrality (LDN). This video illustrates the components of the GeOC tool. To check the GeOC tool, please follow this link: http://geoc.mel.cgiar.org To learn more about the project under which the GeOC tool is developed, please follow this link: https://mel.cgiar.org/projects/geoxc Acknowledgments: 'GeOC is the result of the synergic efforts by CGIAR Research Program on Dryland Systems (CRP-DS), the International Center for Agricultural Research in the Dry Areas (ICARDA) and its Geoinformatics Unit (GU), and is powered by iMMAP, Codeobia, D-Space and Amazon Web Services.'